A Study on the Social Impact of Labour Migration on Life of Woman - Gyawali, Sindhu (Nepal Journal of Multidisciplinary Research, 2022)
This paper attempts to explore the social impact of labour migration on life of woman. The views presented in this paper are based on my research about the quality of life of the women left behind conducted in 2020. Here I argue that labour migration has tremendous social cost. Labour migration has positively contributed to our national economy but we are not cognizant of the challenges faced by Nepalese woman whose husband has migrated outside. Though the labour migration has improved the standard of living of woman and the family left behind, their quality of life is deteriorating. Their feeling of loneliness, frustration, extra burdening and anxiety has escalated.